2015
DOI: 10.1038/bmt.2015.171
|View full text |Cite
|
Sign up to set email alerts
|

Treosulfan-based conditioning regimens for allogeneic haematopoietic stem cell transplantation in children with non-malignant diseases

Abstract: An increasing number of children with non-malignant diseases can be cured by allogeneic haematopoietic stem cell transplantation (HSCT). Treosulfan (L-treitol-1,4-bis-methanesulfonate) is being used more frequently for conditioning, owing to its' lower toxicity profile compared with conventional myeloablative regimens. A retrospective analysis was performed of children registered in the EBMT database, who received treosulfan before HSCT between January 2005 and 2010, to identify possible doserelated toxicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 26 publications
3
66
0
1
Order By: Relevance
“…The use of treosulfan-based regimens has previously been reported in patients with primary immunodeficiency with few significant short-term toxicities. [19][20][21] It is encouraging to find that treosulfan-containing low-toxicity myeloablative regimens confer improved donor chimerism. In these patients, the goal of any conditioning regimen should be to achieve .50% donor B-lymphocyte chimerism to reliably cease immunoglobulin replacement.…”
Section: Resultsmentioning
confidence: 99%
“…The use of treosulfan-based regimens has previously been reported in patients with primary immunodeficiency with few significant short-term toxicities. [19][20][21] It is encouraging to find that treosulfan-containing low-toxicity myeloablative regimens confer improved donor chimerism. In these patients, the goal of any conditioning regimen should be to achieve .50% donor B-lymphocyte chimerism to reliably cease immunoglobulin replacement.…”
Section: Resultsmentioning
confidence: 99%
“…Very young children, as inherently susceptible to toxicity of standard myeloablative agents-busulfan and total body irradiation-are the group of HSCT patients in which TREO is supposed to be particularly useful. So far, TREO-based conditioning has been applied in patients as young as 1 month old (Slatter et al, 2011(Slatter et al, , 2015Dinur-Schejter et al, 2015). The present study was aimed at assessing penetration of TREO and its active epoxy-transformers across the BBB in 10-day-old (JR) and 34-to 35-day-old (YAR) rats and, in the latter, additionally across the BCSFB.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, brain exposure to drugs could be associated with neurologic adverse effects, for instance seizures. Beneficially, in clinical trials high-dose TREO demonstrated low neurotoxicity in adults as well as children, at least in comparison with high-dose busulfan, requiring anticonvulsive prophylaxis (Wachowiak et al, 2011;Casper et al, 2012;Danylesko et al, 2012;Shimoni et al, 2012;Boztug et al, 2015). Nevertheless, in one pediatric study (n = 70, including 46 infants), seizures occurred in four infants aged #4 months (Slatter et al, 2011).…”
Section: Penetration Of Treosulfan and Its Monoepoxide Into Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and use of alternative agents should be encouraged and will hopefully lead to decreased long-term morbidity and mortality. Treosulfan is a structural analogue to busulfan approved for use in Europe and is associated with improved short-term survival when compared to busulfan [42][43] . However, how treosulfan compares to busulfan in the long term remains to be seen.…”
Section: Research Priorities and Future Directionsmentioning
confidence: 99%